TRF2 associates with DREF and directs promoter-selective gene expression in Drosophila. - Hochheimer, A.; Zhou, S.; Zheng, S.; Holmes, M.C.; Tjian, R. (Nature, 2002)
Drosophila TATA-box-binding protein (TBP)-related factor 2 (TRF2) is a member of a family of TBP-related factors present in metazoan organisms. Recent evidence suggests that TRF2s are required for proper embryonic development and differentiation. However, true target promoters and the mechanisms by which TRF2 operates to control transcription remain elusive. Here we report the antibody affinity purification of a Drosophila TRF2-containing complex that contains components of the nucleosome remodelling factor (NURF) chromatin remodelling complex as well as the DNA replication-related element (DRE)-binding factor DREF. This latter finding led us to potential target genes containing TRF2-responsive promoters. We have used a combination of in vitro and in vivo assays to show that the DREF-containing TRF2 complex directs core promoter recognition of the proliferating cell nuclear antigen (PCNA) gene. We also identified additional TRF2-responsive target genes involved in DNA replication and cell proliferation. These data suggest that TRF2 functions as a core promoter-selectivity factor responsible for coordinating transcription of a subset of genes in Drosophila.